Leadership Skills in the Kuwait Oil and Gas Sector - Taqi, Alawi; Talib, Ameen (International Journal Labs, 2023)
Background: Kuwait is a major oil producer. The Oil and Gas Sector is a very complex and highly technical field that it is essential to have technical competencies. Aim: This paper explores the leadership skills of third-line leaders in the Kuwait oil and gas sector. Method: This paper addresses the leadership needs of the framework and how equipped are the third-line leaders in the oil and gas industry. Empirical evidence is collected by semi-structured interviews from the third-line leaders and the findings are presented. The sample size was 42 third-line leaders and data were collected through personal in-depth interviews. Findings: The Kuwaitisation (localisation) policy and Kuwaiti attitude towards wasta and tribalism could have led to ill-equipped third-line managers. Proper training to upgrade the skills is essential. The fourth industrial revolution and the digital age including the internet of things has only augmented the urgency in new skills training.